Profiling of non-criteria antiphospholipid antibodies in patients with SLE: differentiation of thrombotic SLE patients and risk of recurrence of thrombosis. (April 2020) - Tkachenko, O; Lapin, S; Mazing, A; Emanuel, V; Belolipetskaia, E; Beliaeva, I; Myachikova, V; Maslyanskiy, A; Gilburd, B; Schierack, P; Roggenbuck, D
To reveal the clinical significance of criteria and non-criteria antiphospholipid antibodies detected by line immunoassay in comparison with ELISA, systemic lupus erythematosus patients with and without thrombotic events were investigated. Thus, 107 systemic lupus erythematosus patients (48% with deep vein thrombosis or/and arterial thrombosis) and 120 healthy donors were enrolled. Serum antiphospholipid antibodies were detected by ELISA (Orgentec Diagnostika, Germany) and line immunoassay (GA Generic Assays, Germany). Lupus anticoagulant and IgG to cardiolipin and β2GPI but not IgM as well as triple positivity by ELISA and line immunoassay were linked with thrombosis in systemic lupus erythematosus. IgG to phosphatidylinositol and phosphatidylserine by line immunoassay showed significantly higher levels in systemic lupus erythematosus with deep vein thrombosis/arterial thrombosis than without and were independent risk factors for deep vein thrombosis (odds ratio 3.9, 95% confidence interval 1.1, 13.2) and arterial thrombosis (odds ratio 5.1, 95% confidence interval 1.3, 19.8) as well as thrombosis (odds ratio 3.6, 95% confidence interval 1.1, 11.3) and recurrence thereof (odds ratio 6.9, 95% confidence interval 2.1, 22.6), respectively. The occurrence of >4 IgG antiphospholipid antibodies by line immunoassay was an independent risk factor for thrombosis (odds ratio 10.9, 95% confidence interval 1.2, 101.5), arterial thrombosis (odds ratio 14.6, 95% confidence interval 2.5, 86.3), deep vein thrombosis (odds ratio 5.8, 95% confidence interval 1.0, 32.4) and recurrence of thrombosis (odds ratio 35.9, 95% confidence interval 3.8, 342.8). Line immunoassay is a promising multiplex test for the simultaneous detection of criteria and non-criteria antiphospholipid antibodies. Profiling of antiphospholipid antibodies by line immunoassay can differentiate systemic lupus erythematosus patients with thrombosis from systemic lupus erythematosus patients without and assess the risk for thrombosis and recurrence thereof.